Kritik Sosial dalam Lirik Lagu “Indonesia” Karya Rhoma Irama - Moh Muzakka (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Rhoma Irama is a multi-talented artist who is very popular today. He has created many songs with many themes as well. One of the songs that voiced about nationalism, titled "Indonesia". However, in the lyrics of the song, he criticized the government because of social inequality that occurred in this rich and fertile country. Therefore, in this paper the author will uncover any social criticism that appears in the lyrics of the song "Indonesia" with the sociological approach to literature.The results showed that in the song lyrics, Rhoma Irama made three criticisms to the government, namely (1) criticism of social class disparities, (2) criticism of the rampant corruption in bureaucracy, and (3) criticism of unfair government policies.